PENINGKATAN EFEKTIVITAS PERKULIAHAN KIMIA DASAR MELALUI PEMBELAJARAN BERORIENTASI CHEMOENTREPRENEURSHIP (CEP) MENGGUNAKAN MEDIA CHEMOEDUTAINMENT (CET) - Sumarni, Wono (Lembaran Ilmu Kependidikan, 2009)
The research aimed to improve the entrepreneurship spirit and the mastery ofchemistry concepts for chemistry teacher students by applying the basic chemistrylearning model oriented chemoentrepreneurship (CEP) using chemoedutainment(CET) media. This research used the Education Research and Development design.The data were collected through concept mastering test, questionnairre andobservation sheet. The research result showed that the application of the learningmodel improved the concept mastery of chemistry teacher students with high andmedium attachment levels. The advantages of this model are (1) improving themastery of basic chemistry concept for chemistry teacher students, (2) improving thestudents’ activity during learning, (3) giving a chance to the lecturers to serve thestudents through individual services.Kata kunci: Chemo-entrepreneurship (CEP), Chemo-entertaintment (CET),Pembelajaran Kimia Dasar